Relationship between the interleukin‐6‐174 gene and mannose‐binding lectin codon 54 gene polymorphisms and condyloma acuminatum. (3rd October 2013) - Aydogan, K.; Ozakin, C.; Saricaoglu, H.; Sigirli, D.; Oral, B.
Abstract Background Several genes encoding different Th1 and Th2 cytokines may play crucial roles in host susceptibility to Condyloma acuminatum (CA). Mannose‐binding lectin (MBL) is a serum lectin that mediates complement activation, and it is a member of innate immune system. MBL gene polymorphisms are considered to be associated with several infectious diseases. Objective In this study, we investigated the association between cytokines and MBL gene polymorphisms with CA. Methods Forty patients with CA and 40 healthy controls were enrolled in this study. These patients had not responded to at least a therapy modality and all patients had recurrent lesions. Polymorphism of cytokine [Th1 cytokines; tumour necrosis factor‐α and interferon (IFN)‐γ, Th2 cytokine; IL‐6, T regulatory/suppressor cytokines; IL‐10 and transforming growth factor‐β] genes studies were performed by Polymerase chain reaction sequence‐specific primers method and MBL genotyping were studied by PCR‐restriction fragment length polymorphism method. Results With the aid of agglomerative hierarchical cluster analysis, we categorized subjects into two main clusters (cluster 1; formed by the majority of patients with CA, cluster 2; formed by the majority of healthy controls), which were found to have significantly different distributions of IL‐6 and MBL genotypes. Frequencies of IL‐6 (‐174) G/G (P < 0.001) and MBL AA (P < 0.001) polymorphisms were significantly greater in the cluster 1. In contrast, significantly lower frequencies of the IL‐6 G/C (P = 0.046) genotype and MBL AB (P < 0.001) genotype were observed in cluster 1. Conclusion These results suggest that the IL‐6 G/G and MBL AA gene polymorphisms are potential risk factors and that the IL‐6 G/C and MBL AB polymorphisms are a protective factor for occurrence and recurrence of CA.